Factor the polynomial and use the factored form to find the zeros. (Enter your a

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

P(x) = 

1
5
(2x4 + 3x3 − 16x − 24)2
Mar 15th, 2015

(2x^4 + 3x^3 − 16x − 24)^2 = 0 

(x^3(2x + 3) − 8(2x + 3))^2 = 0 

((x^3 − 8)(2x + 3))^2 = 0 

taking square root on both sides, we get

(x^3 − 8)(2x + 3) = 0 

(x - 2)(x^2 + 2x + 4)(2x + 3) = 0

x = 2    x = - 3/2      x^2 + 2x = - 4

                                x(x + 2) = - 4

                               x = - 4    x = - 6

Mar 15th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 15th, 2015
...
Mar 15th, 2015
Oct 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer